2022
DOI: 10.1088/1402-4896/ac79d7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of entropy generation in the nonlinear thermal radiative micropolar nanofluid flow towards a stagnation point with catalytic effects

Abstract: The major goal of this work is to analyze the entropy generation in a micropolar nanofluid’s hydromagnetic stagnation point flow with the involvement of the catalytic and nonlinear thermal radiation effects. The magnetite nanoparticle Fe3O4 is added to the water to form the Fe3O4-water nanofluid. A vertical stretchable sheet is assumed to initiate the two-dimensional time-independent flow. The impacts of Joule heating and viscous dissipation are considered in the development of the governing equations of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…15 and 16 for C(t), and A(t), respectively. The basic flow equations of Nano liquid are [34][35][36][37][38][39]:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 and 16 for C(t), and A(t), respectively. The basic flow equations of Nano liquid are [34][35][36][37][38][39]:…”
Section: Resultsmentioning
confidence: 99%
“…With bounded conditions [34,36,37,40] ũ| y=0 = u w = cx, ṽ| y=0 = −v 0 , w| y=0 = 0, T| y=0 = Tw , C| y=0 = Cw ũ| y=h = 0, ṽ| y=h = 0, w| y=h = 0, T| y=h = Tl , C| y=h = Cl .…”
Section: Resultsmentioning
confidence: 99%
“…The time-independent, significant 2D flow demeanor is supposed to start with a vertically stretchable sheet. When creating the governing equations for the relevant issue, the Joule heating and viscous dissipation impacts are considered, as described previously [18]. Using updated heat and mass flux models, the entropy production approach is subjected to Maxwell nanofluid incorporated with gyrotactic microorganisms influenced by homogeneous-heterogeneous processes.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the velocity of the system diminishes relative to the higher magnitude of the uid parameter. The heat transfer mechanism and chemical reactive ow phenomenon in uenced by different physical circumstances in a non-Newtonian uid were scrutinized by Ishtiaq et al [10]. The non-Newtonian model of Sisko uid with variable characteristics was demonstrated by Ahmad et al [11].…”
Section: Introductionmentioning
confidence: 99%